LAYANAN PESAN SINGKAT PENGINGAT MENINGKATKAN KEPATUHAN MINUM OBATPASIEN DIABETES MELITUS DI RSUD ULIN BANJARMASIN - Riza Alfian (Jurnal Ilmiah Manuntung, 2015)
Diabetes melitus is one ofthe metabolic disorders with characteristic hyperglycemia that occurs due to abnormal insulin secretion, insulin resistance or both. The non adherence patients of taking antidiabetic drugs are the main factors that could cause high blood glucose levels, so it is necessary an intervention to achievedoutcome therapy desired. Giving of short message service reminder intervention in diabetes mellitus patients was expected to improved the medication adherence and achieved normal blood glucose levels.This study was conducted to determine the effect of a short message service reminder on medication adherence of ambulatory diabetes melitus patients in Ulin General Hospital Banjarmasin.This study was conducted with quasi-experimental design,the data were taken prospectively during May to June, 2014. The subjects were ambulatory diabetes melitus patients in Ulin General Hospital Banjarmasin who had received oral antidiabetic drugs. Subject who met the inclusion and exclusion criteria were 39 patients and had given an intervention for seven days. The data collected by interviews and pill counting on filling sheet. The blood glucose levels data was taken from their medical records.The result showed that giving of a short message service reminder intervention improve patient adherence (p<0,05). Fasting blood glucose level and blood glucose level two hours post prandial have decreased significantly (p<0,05). There were correlation between the patient adherence and the decreasing in fasting blood glucose levels (p=0,050; r=0,316) and blood glucose two hours post prandial levels (p=0,010; r=0,040).Based on these result, it can be concluded that the giving of short message service reminder in diabetes melitus patientshas been improved patient adherence.